Mixed-potential integral equation technique for hybrid microstrip-slotline mutli-layered circuits with horizontal and vertical shielding walls - Schoeman, Marlize (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScIng)--University of Stellenbosch, 2003.